A numerical modeling study on the influence of porosity changes during thermochemical heat storage. (1st February 2020) - Seitz, Gabriele; Helmig, Rainer; Class, Holger
Highlights: Thermochemical reaction system CaO/Ca(OH)2 studied numerically for charge/discharge. Model concept capable of representing changes of hydraulic properties during reaction. Predicted reaction performance and stored/released heat depend on poro-perm relation. Abstract: Thermochemical energy storage can achieve high storage densities as well as nearly loss-free long-term storage, while offering charge or discharge on demand. Suitable materials consist of solid and gaseous components, where the dosage of reacting gas in the reactor can easily be regulated to control the reaction. Most materials currently investigated for thermochemical heat storage feature a volume change of the solid reactive material during the reaction. To study this effect and its influence on the reaction performance, we present a numerical model that can capture the changing hydraulic properties of the solid reactor fill, represented by the parameters porosity and permeability. This model is applied to a quasi-1D setup for the reaction system CaO/Ca(OH)2 . This study shows that both porosity alteration and induced permeability change have a significant effect on the performance of the reaction. Solid volume changes are about 50% with initial porosities at 0.6 for charge and 0.8 for discharge. Depending on the porosity-permeability relationship, the corresponding changes in permeability are about one to two orders of magnitude. The porosity influences the shape of the reaction front and the amount of released (or consumed, depending on charge or discharge) heat. The permeability of the solid material strongly affects the velocity of the reaction front and thus the time necessary for complete conversion. We conclude that the hydraulic properties of a specific reaction system have to be well understood to (i) include the relevant processes in the conceptual model, and thus (ii) allow for more reliable predictions on the performance of the reaction.